The Influence of Suandei Fall on Art of Carving Artists in Woinap Village, Yapen Island District - Frans Falentinus Marahole; Amost Marahole; Roy Marthen Rahanra (Lakhomi Journal Scientific Journal of Culture, 2021)
The art of carving, known as carving, or decoration with various flora, fauna, figurative and even geometric motifs which is an ornate image with some parts being concave and some parts convex both horizontally and vertically and elliptically arranged in a very beautiful image. (Study of Cultural Anthropology)(1) The carvings, which are known in the works of Decorative Arts, still survive and are in demand and are found in various areas such as the Biak Numfor Islands, Yapen Islands, Waropen Wondama Bay and various other areas that are included in the Kuripasai cultural family, Mananarmakeri, and Sairei. A special highlight in this writing is the carving motifs that are still practiced by carving craftsmen in Woinap Village, Wonawa District, Yapen Islands Regency, where until now there are very few carvers. This carving motif was inspired by the legend of "Suandei" by Drs. Frits Maurid Kirihio, alumni of the University of Leyden, the Netherlands, in the 1950s, who was recorded in the book “Dongen Tanah Kita,(2) Descriptive analysis method is a method used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to generalization or generalization, Sugiyono (2014:21)(3) Excellence Carving motifs based on beliefs that have been practiced so far in the village of Woinap, Yapen Islands Regency. or skulls, all of which are manifested and the decorations that are usually displayed on family tools such as boats, wooden pans (sempe) art tools (tifa) net buoys, all take symbolic or philosophical meanings from their original form.(4) The indigenous people of Woinap are a community categorized as living in the outermost area of ​​the Yap . Islands Regency en and still isolated from the rapid development of the era. However, it cannot be separated from local wisdom techniques that are often adopted from neighboring areas which are more innovative in people's lifestyles because culture is dynamic and always moves with the times, so the people of Woinap also move with the habit of living with the times by way of -a new way that is still considered cultural even though indigenous cultural values ​​have been eroded.(5) The cultural heritage of the Papuan people in the saireri strait region, especially the unique carving art of the Woinap community, has an economic potential that can bring ecotourism and increase the PAD of the Islands district government Yapen.(6)